2017
DOI: 10.1002/pbc.26822
|View full text |Cite
|
Sign up to set email alerts
|

Screening with whole‐body magnetic resonance imaging in pediatric subjects with Li–Fraumeni syndrome: A single institution pilot study

Abstract: WB-MRI in pediatric subjects is a well-tolerated approach to cancer surveillance despite the need for general anesthesia in some patients. A large multicenter trial would determine true test characteristics and efficacy of this approach for early cancer detection in children at high cancer risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 22 publications
0
31
0
2
Order By: Relevance
“…Although this and the expansion of Medicaid have significantly provided greater access to patients in need of cancer screening, many coverage gaps remain . Thus, some patients, such as those with LFS, continue to face financial obstacles to clinically important cancer screening . Moody, in his editorial to JAMA in 1903, emphasized the importance of disease prevention, declaring that no subject “can be more important to the welfare of humanity.” Clinical and reimbursement decision makers need to carefully consider the added costs and benefits to the implementation of clinical surveillance programs and the impact these decisions, including the corresponding cost‐sharing requirements, have on patient care and outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this and the expansion of Medicaid have significantly provided greater access to patients in need of cancer screening, many coverage gaps remain . Thus, some patients, such as those with LFS, continue to face financial obstacles to clinically important cancer screening . Moody, in his editorial to JAMA in 1903, emphasized the importance of disease prevention, declaring that no subject “can be more important to the welfare of humanity.” Clinical and reimbursement decision makers need to carefully consider the added costs and benefits to the implementation of clinical surveillance programs and the impact these decisions, including the corresponding cost‐sharing requirements, have on patient care and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…If cancer surveillance does indeed detect a greater frequency of tumors that are treated as compared with what would normally be treated (i.e., unrecognized overdiagnosis of nonmalignant lesions leading to possible overtreatment), this could render the strategy less cost‐effective. However, recent analyses among patients with LFS have found that overdiagnosis and unnecessary treatment of indolent lesions to be uncommon . Additional estimates of tumor development and patient survival using real‐world data are needed to determine the likelihood of this occurring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current LFS standard screening protocols 26 have been instituted in clinics throughout the world [27][28][29][30][31] . At MDACC, the Li-Fraumeni Education and Early Detection (LEAD) Program consists of "a centralized approach to patient management, screening exams performed at the same institution, including whole-body MRI and brain MRI, using same technique and same machines enabling more consistent comparison of findings between and across interval exams in patients and a multidisciplinary team that reviews all findings and patient issues to develop follow up recommendations" 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, improved long‐term survival in TP53 mutation carriers was associated with early tumor detection via intensive surveillance . Several groups internationally are investigating whole‐body MRI in TP53 mutation carriers . A meta‐analysis of whole‐body MRI data including 578 participants from 13 cohorts across six countries estimated an overall detection rate for new localized primary cancers as 7% (95% CI 5%‐9%) at baseline, several of which were sarcomas .…”
Section: Surveillance In Hereditary Sarcomamentioning
confidence: 99%